The POLγ Y951N patient mutation disrupts the switch between DNA synthesis and proofreading, triggering mitochondrial DNA instability - Josefin M. E. Forslund; Tran V. H. Nguyen; Vimal Parkash; Andreas Berner; Steffi Goffart; Jaakko L. O. Pohjoismäki; Paulina H. Wanrooij; Erik Johansson; Sjoerd Wanrooij (Proceedings of the National Academy of Sciences, 2025)
Mitochondrial DNA (mtDNA) stability, essential for cellular energy production, relies on DNA polymerase gamma (POLγ). Here, we show that the POLγ Y951N disease-causing mutation induces replication stalling and severe mtDNA depletion. However, unlike other POLγ disease-causing mutations, Y951N does not directly impair exonuclease activity and only mildly affects polymerase activity. Instead, we found that Y951N compromises the enzyme’s ability to efficiently toggle between DNA synthesis and degradation, and is thus a patient-derived mutation with impaired polymerase-exonuclease switching. These findings provide insights into the intramolecular switch when POLγ proofreads the newly synthesized DNA strand and reveal a new mechanism for causing mitochondrial DNA instability.